EFISIENSI SERAPAN HARA BEBERAPA JENIS PUPUK PADA BIBIT KELAPA SAWIT - Eko Noviandi Ginting; Suroso Rahutomo; Edy Sigit Sutarta (Jurnal Penelitian Kelapa Sawit, 2018)
Fertilizer efficiency is a ratio between the amount of nutrient that absorbed by the plant and the amount of nutrient that applied through fertilizer. The efficiency of a fertilizer can be defined as the number of nutrients that can be absorbed by the plan. The objective of this study was to compare the efficiency of three types of fertilizers on the oil palm seedling. This research was conducted on Indonesian Oil Palm Research Institute at Medan, North Sumatra, Indonesia. Four treatments with three replications were arranged by a completely randomized design. The treatments are: 1) P0 = control/no fertilizer; 2) P1 = Briquette compound fertilizer, 3) P2 = Granular compound fertilizer, and 4) P3 = single-nutrient fertilizer; Urea, TSP, MoP, and Kieserite. The results showed that (I) nutrients uptake (NU) of N, P, K, and Mg on briquette compound fertilizer relatively higher about 11%; 21%; 9%; and 23% compare to granular compound fertilizer and 5%; 1%; 1% and 19% higher than P3 respectively; (ii) recovery efficiency (RE) of N, P, K, and Mg on briquette compound fertilizer were 18%; 42%; 16%; and 20% higher than granular compound fertilizer and 8%; 1%; 2%; and 19% than single-nutrient fertilizer; while (iii) agronomic efficiency (AE) of N, P, K, and Mg on Briquette compound fertilizer were higher about 26% (for each nutrient) compare to Granular compound fertilizer and 18% higher (for each nutrient) than single-nutrient fertilizer.